Association of carotid and intracranial stenosis with Alzheimer’s disease biomarkers - Kang, Koung Mi (Alzheimers Res Ther, 2020)
BACKGROUND: To clarify whether atherosclerosis of the carotid and intracranial arteries is related to Alzheimer’s disease (AD) pathology in vivo, we investigated the associations of carotid and intracranial artery stenosis with cerebral beta-amyloid (Aβ) deposition and neurodegeneration in middle- and old-aged individuals. Given different variations of the pathologies between cognitive groups, we focused separately on cognitively normal (CN) and cognitively impaired (CI) groups. METHODS: A total of 281 CN and 199 CI (mild cognitive impairment and AD dementia) subjects underwent comprehensive clinical assessment, [(11)C] Pittsburgh compound B-positron emission tomography, and magnetic resonance (MR) imaging including MR angiography. We evaluated extracranial carotid and intracranial arteries for the overall presence, severity (i.e., number and degree of narrowing), and location of stenosis. RESULTS: We found no associations between carotid and intracranial artery stenosis and cerebral Aβ burden in either the CN or the CI group. In terms of neurodegeneration, exploratory univariable analyses showed associations between the presence and severity of stenosis and regional neurodegeneration biomarkers (i.e., reduced hippocampal volume [HV] and cortical thickness in the AD-signature regions) in both the CN and CI groups. In confirmatory multivariable analyses controlling for demographic covariates and diagnosis, the association between number of stenotic intracranial arteries ≥ 2 and reduced HV in the CI group remained significant. CONCLUSIONS: Neither carotid nor intracranial artery stenosis appears to be associated with brain Aβ burden, while intracranial artery stenosis is related to amyloid-independent neurodegeneration, particularly hippocampal atrophy.